Namibia : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Namibia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This 2008 Article IV Consultation discusses that real GDP growth in Namibia is expected to moderate to about 3 percent in 2008 from 4.1 percent in 2007, reflecting a downturn in the mining sector owing to the global economic slowdown. Executive Directors have commended the authorities' sound macroeconomic management, which had contributed to solid growth and strong external and fiscal positions. Directors have also encouraged the authorities to press ahead with their structural reform agenda so as to improve the country's competitiveness, diversify the economy, and bolster growth prospects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet